Fecundity, spore recruitment and size in Gelidium sesquipedale (Gelidiales,Rhodophyta) - Santos, R. (2007)
Gelidium sesquipedale fecundity was quantified by counting tetrasporangial sori and cystocarps per meter squared and by estimating the number of spores contained inside them . These were obtained by regression on a size metric of reproductive structures . Tetrasporangial sori length and cystocarp thickness were the best estimators of spore number. To assess spore recruitment, 12 pottery tiles were fixed to the bottom, and the appearance of small fronds was monitored. No clear seasonal pattern of reproduction was found . Tetraspore production peaked in March 1990 with 10.4 x 106 spores m-2, whereas the carpospore peak was lower, 4.9 x 10 5 spores m-2 in July 1989. Recruitment followed tetraspore peaks . The probability of a G. sesquipedale tetraspore making the transition to a recruit was 4.7 x 10-5. Frond length was significantly related to tetrasporangial sori number, while cystocarp number was only related to frond branching order. Minimum size for reproduction was 6.9 cm for gametophytes and 5.4 cm for tetrasporophytes; very rarely were cystocarpic fronds smaller than 9 cm, while tetrasporic fronds were often longer than 15 cm . Cystocarpic fronds were significantly shorter and had more branches than tetrasporic fronds .